Effect of variable carbohydrate intake on exercise performance in female endurance cyclists - Reznik Dolins, K.; Boozer, C. N.; Stoler, F.; Bartels, M.; DeMeersman, R.; Contento, I. (International Journal of Sport Nutrition and Exercise Metabolism, 2003)
This study measured the effect of variable carbohydrate intake on time to exhaustion, variations in heart rate (HR), respiratory exchange ratio (RER), and rating of perceived exertion (RPE) in female endurance cyclists during an exercise trial. Subjects were 11 eumenorrheic women with maximal oxygen consumption (VO2max) 60.1 ± 5.1 ml/kg who habitually cycled at least 100 miles per week. In a crossover design, each woman was randomly assigned to a eucaloric diet providing 8, 5, or 3 g of CHO/kg of body weight. Subjects cycled at least 100 miles while adhering to the diet for 6 days. The exercise trial was performed on the 7th day, consisting of a 60 min cycle at 70% VO2max, followed by an increase in intensity to 90% VO2max until that intensity could no longer be maintained. Results indicated no difference in mean time to exhaustion, heart rate, or RPE. RER increased over time-elapsed (F = 40.4, p < .001) and across diets (F = 6.1, p = .015). Conclusions: Female endurance cyclists did not experience a difference in time to exhaustion, HR, or RPE with different levels of CHO intake during an endurance trial. RER varied with diet at submaximal intensities. Further research is needed to determine the optimal level of CHO intake for this population.